Ideas of reforming education in Western Europe during the XIX century - Колесник, Ірина (Pedagogy of Higher and Secondary Education, 2014)
Kolesnik I. A. Ideas of reforming education in Western Europe during the XIX century. The article deals with the role of national transformation, the basic factors of development of pedagogical science, global general trends of reforming education, typical for Europe and the United States the study period. It is proved that the reform of the school system promoted intensive industrial growth and development of pedagogical science, and also reflects the need of the society in the preparation through school versatile development, enterprising people willing to be active in various fields of economic, political and social life.